The role of repeat fine needle aspiration in the management of indeterminate thyroid nodules. Issue 1 (December 2016) - Jooya, Alborz; Saliba, Joe; Blackburn, Audrey; Tamilia, Michael; Hier, Michael P.; Mlynarek, Alex; Forest, Véronique-Isabelle; Rochon, Louise; Florea, Anca; Wang, Hangjun; Payne, Richard J.
Abstract Background Management decisions are not straightforward when the Ultrasound Guided Fine Needle Aspiration (USFNA) demonstrates a Bethesda score of either category III or IV, and a diagnostic hemi-thyroidectomy or a repeat USFNA (r-USFNA) could be performed. The aim of this study is to assess the effectiveness of r-USFNA in the management of indeterminate thyroid nodules by evaluating the likelihood of obtaining a definite diagnosis. Methods We reviewed the medical records of all patients with thyroid nodules between 2011 and 2015 at the Jewish General Hospital (Montreal, Canada). Three hundred fifty-one patients who had undergone a surgical procedure (hemi or total thyroidectomy) and a diagnosis of B3 or B4 on the primary USFNA (p-USFNA) were included in the study. Ninety-six of the included patients also had a repeat USFNA prior to the surgery. Demographic data, type of procedure, and McGill Thyroid Nodule Score (MTNS) were obtained from the medical records. Malignancy rates were calculated based on the final surgical histopathology report. Results Upon r-USFNA, an average 76 % of patients did not change Bethesda categories, 7.4 % downgraded to a benign category. The results showed that, on an average 17.3 % of patients with p-USFNA of B3 and 20 % of patients with p-USFNA of B4, upgraded to a malignant or suspicious for malignancy category, thus changing the clinical management to total thyroidectomy. Our data demonstrates that r-USFNA facilitates choosing the correct surgery of total thyroidectomy in about 20 % of nodules that have upgraded from B3/B4 to a more definite malignant category. Conclusions r-USFNA in patients with indeterminate diagnoses (B3 or B4) increases categorization into more definite categories. Approximately 20 % of patients are found to have malignant thyroid nodules and suspicious for malignancy thyroid nodules upon repeating the biopsy, hence a diagnostic hemi-thyroidectomy was avoided and a more definitive surgery could be performed. Furthermore, repeat USFNA results in a fewer number of hemi-thyroidectomy and completion thyroidectomy procedures.